DEVELOPING AN ENGLISH FOR TOURISM DIGITAL MODULE ORIENTED TO THE LOCAL WISDOM VALUES OF MAGELANG - Rolisda Yosintha; Boris Ramadhika; Sukma Shinta Yunianti; Agnira Rekha; Carolus Prima Ferri Karma (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
ABSTRACT This study aimed to develop an English for Tourism (EFT) digital module oriented to the local wisdom values of Magelang. This study was part of a research and development study employing the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Beginning with a need analysis phase using a questionnaire, the researchers found students' needs of 10 (ten) relevant language functions that will help them communicate effectively in the tourism industry. These topics were developed into a flipbook by inserting Magelang's wisdom values. To test its feasibility, the researchers conducted an expert judgment procedure by inviting two experts in the field of EFT and media development. The results showed that the Flipbook was feasible to be used with a mean score of more than three for each criterion of a quality module determined by the Education, Curriculum, and Assessment Standards Agency of Indonesia. In addition, following the expert's suggestions, the researchers added a section developed to enrich the student's vocabulary. This study presents the significance of developing learning materials that integrate local values to build students' noble character.ABSTRAKPenelitian ini bertujuan untuk mengembangkan modul digital English for Tourism (EFT) yang berorientasi pada nilai-nilai kearifan lokal Magelang. Penelitian ini merupakan bagian dari penelitian dan pengembangan dengan model ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Tahap analisis kebutuhan menghasilkan identifikasi kebutuhan siswa akan 10 (sepuluh) fungsi bahasa yang dapat membantu mereka berkomunikasi dengan efektif di bidang industri pariwisata.. Topik-topik tersebut dikembangkan menjadi flipbook dengan memasukkan nilai-nilai kearifan Magelang. Untuk menguji kelayakannya, peneliti melakukan expert judgment dengan dua orang ahli di bidang EFT dan pengembangan media. Hasil penelitian menunjukkan bahwa flipbook ini layak digunakan dengan nilai rata-rata lebih dari tiga untuk setiap kriteria kualitas modul yang ditetapkan oleh Badan Standar, Kurikulum, dan Asesmen Pendidikan Indonesia. Selain itu, peneliti juga mengikuti saran dari ahli untuk menambahkan bagian khusus untuk peningkatan kosakata. Kajian ini memaparkan pentingnya pengembangan bahan ajar yang mengintegrasikan nilai-nilai lokal untuk membangun akhlak mulia siswa.How to Cite: Yosintha, R., Ramadhika, B., Yunianti, S.S., Rekha, A., & Karma, C. P. F. (2023). Developing an English for Tourism Digital Module Oriented to the Local Wisdom Values of Magelang. IJEE (Indonesian Journal of English Education), 10(2), 278-300. doi:10.15408/ijee.v10i2.32243.